Factors affecting the management of human resources at small and medium enterprises during Covid-19 pandemic in Vietnam - Nga Phan Thi Hang (Cogent Business & Management, 2024)
During the past pandemic, digital business activities have developed enormously, and many businesses have undergone a significant transformation to participate in the digital revolution. However, for the digital transformation to take place successfully, Industry 4.0 comes from breakthroughs in many fields, including the digital wave of the manufacturing sector. Many countries have paid attention to and concretized priorities for developing a digital economy. Vietnam also faces challenges that the digital trend brings, including the risk of competition for small and medium enterprises, especially high-quality human resources in today's businesses. This article analyzed the current situation and applied descriptive statistics to summarize and apply the structural equation model (SEM) from a set of data, a research sample in numbers, and visual charts that surveyed 850 enterprise managers. Human resource management is a multifaceted process that has wide-ranging effects. Presently, several variables are influencing the field of human resource management. These elements often undergo changes and can be categorized into fundamental influencing factors: The attributes of the external factors, including the economy, people, legislation, culture, rivals, science, and technology. The internal environment encompasses several variables: the working environment, labor recruitment and selection, training and development, remuneration, bonuses, and welfare. The article's goal is to explore factors that influence human resource management. Based on the results, the article's contributions had several policy recommendations for developing human resources at small and medium enterprises for Vietnam's post-Covid-19 pandemic. The application of the research is to strengthen and build a cultural working environment and create conditions and opportunities for human resources to develop; business leaders must be exemplary in words and deeds. Human resource development strategies must be implemented in an environment of fairness, discipline, ethics, and respect for the law as standards; create a cultural environment, leading the development of human resources.
Keywords: 650; Human resourcemanagement; enterprises; covid-19 pandemic; policyimplications; Vietnam